Advances in catalytic and protecting-group-free total synthesis of natural products: a recent update. Issue 61 (15th June 2020) - Fernandes, Rodney A.; Kumar, Praveen; Choudhary, Priyanka
Abstract : This feature article highlights the recently achieved efficient total syntheses of many natural products based on catalytic steps and protecting-group-free strategies, leading to overall economy and efficiency in synthesis. Abstract : Catalytic processes in protecting-group-free syntheses of natural products are fast emerging towards achieving the goal of efficiency and economy in total synthesis. Present day sustainable development in synthesis of natural products does not permit the luxury of using stoichiometric reagents and protecting groups. Catalysis and step-economy can contribute significantly toward economy and efficiency of synthesis. This feature article details the ingenious efforts by many researchers in the last couple of years toward concise total syntheses, based on catalytic steps and protecting-group-free-strategies. These would again serve as guidelines in future development of reagents and catalysts aimed at achieving higher efficiency and chemoselectivity to the point that catalysis and protecting-group-free synthesis will be an accepted common practice.